THE INFLUENCE OF CLARITY OF BUDGET TARGETS AND IMPLEMENTATION OF PUBLIC SECTOR ACCOUNTING ON PERFORMANCE ACCOUNTABILITY STUDY AT PT. PEGADAIAN (PERSERO) MAKASSAR CITY - Sultan AR, Muh. Ikhsan; Yusuf, Marwah; Anim, Anim (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
Purpose – This study aims to examine and analyze the effect of budget target clarity and the application of public sector accounting on performance accountability studies at PT. Pegadaian (Persero) Makassar City. Design/methodology/approach – Data analysis methods using multiple regression techniques. Findings – The results showed that all hypotheses were accepted because the Clarity of Budget Targets and the Application of Public Sector Accounting had a positive and significant effect on Performance Accountability. This means that by increasing the Clarity of Budget Targets and the Application of Public Sector Accounting, it can improve the Performance of Study Performance Accountability at PT. Pegadaian (Persero) Makassar City with a big impact. Originality – Data collection used primary data obtained from a purposive sample where 10 offices were obtained, 3 respondents were determined for each office so that a total of 30 employees of PT. Pegadaian (Persero) Makassar City. Keywords: Clarity of Budget Targets, Implementation of Public Sector Accounting, Performance Accountability Paper Type Research Result